The Believer : How an Introvert with a Passion for Religion and Soccer Became Abu Bakr al-Baghdadi, Leader of the Islamic State - McCants, William F. (William Faizi), 1975- (Brookings essay., 2018)
In The Believer, Will McCants tells the story of Abu Bakr al-Baghdadi, the leader of the Islamic State (a.k.a. ISIS), a group so brutal and hardline that even al-Qaida deemed them too extreme. Baghdadi, an introverted religious scholar, with a passion for soccer, now controls large swaths of land in Iraq and Syria. McCants shows how Baghdadi became radicalized in the Saddam Hussein era and found his path to power after connecting with other radicals in an American prison during the Iraq War, culminating in his declaration of a reborn Islamic empire bent on world conquest.